Implementation of the Asthma Practice Guideline in the Army Medical Department - Farley, Donna O.; Cretin, Shan; Vernez, Georges; Pieklik, Suzanne; Quiter, Elaine (RAND Corporation, 2023)
In partnership with the Army Medical Department, RAND worked to implement clinical practice guidelines. This report evaluates the asthma guideline demonstration. It documents the actions, assesses effects, and measures the quality and limitations of data for monitoring outcomes. The authors found that the implementation scored successes but resource limitations and organizational barriers curbed progress. They conclude that flexibility, monitoring, and training are the keys to implementing the guidelines. They also found that patient education needed improvement.